2019
DOI: 10.1371/journal.pone.0216500
|View full text |Cite
|
Sign up to set email alerts
|

Nothing else matters? Tree diameter and living status have more effects than biogeoclimatic context on microhabitat number and occurrence: An analysis in French forest reserves

Abstract: Managing forests to preserve biodiversity requires a good knowledge not only of the factors driving its dynamics but also of the structural elements that actually support biodiversity. Tree-related microhabitats (e.g. cavities, cracks, conks of fungi) are tree-borne features that are reputed to support specific biodiversity for at least a part of species’ life cycles. While several studies have analysed the drivers of microhabitats number and occurrence at the tree scale, they remain limited to a few tree spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 48 publications
14
44
0
Order By: Relevance
“…Surprisingly, the larger hotspots have been predicted in low cavity density, but well‐connected forest areas, such as in Sweden and Finland where conifers are dominant (except for some birch— Betula spp.—and aspen— Populus tremula —dominated forests). As expected, other important hotspots were detected in areas of unmanaged forests allowing high cavity densities (Kozák et al., ; Paillet et al., , ), for which wild honeybees should be added to the list of unmanaged forest‐dependent species. It is important to note that our estimates do not include other determinants of wild honeybee population densities, particularly the flower resource quality of forests, which is mainly unknown for European forests.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Surprisingly, the larger hotspots have been predicted in low cavity density, but well‐connected forest areas, such as in Sweden and Finland where conifers are dominant (except for some birch— Betula spp.—and aspen— Populus tremula —dominated forests). As expected, other important hotspots were detected in areas of unmanaged forests allowing high cavity densities (Kozák et al., ; Paillet et al., , ), for which wild honeybees should be added to the list of unmanaged forest‐dependent species. It is important to note that our estimates do not include other determinants of wild honeybee population densities, particularly the flower resource quality of forests, which is mainly unknown for European forests.…”
Section: Discussionsupporting
confidence: 57%
“…Our results showed that conifer‐dominated forests are generally poorer in microhabitats, especially in tree cavities (see also Paillet et al., ). This is likely related to the foraging and nesting habits of cavity excavators, which tend to prefer broadleaved trees (e.g., Kosinski et al., ; Rolstad, Rolstad, & Saeteren, ), as well as to the higher persistence of decayed cavities on broadleaved trees (Paillet et al., ; Wesołowski, ). Unsurprisingly, unmanaged forests displayed significantly higher cavity densities than their managed counterparts, due to the higher occurrence of large trees and snags in these forests (Kozák et al., ; Paillet et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Appendix S2: Protocol for the French nature forest reserves stand structure description On each circular plot, forest stand structure was characterized using the following protocol (Paillet et al, 2015(Paillet et al, , 2019:…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…The relationships between species diversity and forest complexity have been investigated by estimating the species richness (Moning & Müller 2009). Management types strongly influence the occurrence and abundance of microhabitats (MHs), in turn the diversity of coexisting species (Paillet et al 2019, Parisi et al 2020. Microhabitats occurring on living or standing dead trees constitute a particular and essential substrate or life site for species or communities to develop, feed, shel-ter or breed, during at least a part of their life cycle (Larrieu et al 2018).…”
Section: Introductionmentioning
confidence: 99%